Removals of Ammonia and Colour from Stabilized Leachate by using Aerated Chemical Coagulation - Norazmi, Muhammad Norarfan; Mohd Zin, Nur Shaylinda (Recent Trends in Civil Engineering and Built Environment, 2023)
The amount of Municipal Solid Waste (MSW) produced in Malaysia increased from year to year as an effect of the urbanization. This causes the landfill to receive a large amount of MSW beyond its capacity. Landfill produced leachate which contains various substances. This study utilised an Aerated Chemical Coagulation (ACC) technique as a leachate treatment to cope with leachate management. This method used to remove ammonia and colour from stabilized leachate under the influence of Polyaluminium Chloride (PAC) dosage, pH and aeration rate. Sample of leachate have been analyse to get the characteristics of leachate. In addition, the efficiency of ACC was compared to single aeration and single chemical coagulation in removing ammonia and colour. This comparison determined based on influence of aeration rate, aeration duration, PAC dosage, pH and mixing duration. Based on the result, the optimum value for ACC under the influence of PAC dosage, pH and aeration rate were 400 mg/L, pH 5 and 1.0 L/min. ACC shown the best removal of ammonia with 77% while single chemical coagulation removed colour better than ACC and single aeration with 82%. Lastly, the optimum colour and ammonia removal obtained from ACC was not achieve the standard of EQR 2009. It was because this study has been used raw leachate and if other treatment can be integrated with ACC, probably it can achieve the effluent standard for colour and ammonia. As a conclusion, ACC has a potential to treat old leachate based on the removal parameters which were ammonia and colour.